The psychological insight into frustration tolerance development in adolescence - Bozhok, Natalia (My University, 2017)
In the article, the period of adolescence is under study and the peculiarities of the mentioned age category are also specified. Psychological analysis of the phenomenon of «frustration tolerance» is made on the basis of the views of foreign and domestic researchers. The interconnection of psychological peculiarities of adolescence and «frustration tolerance» is analyzed and defined. As a result, the most crucial components affecting “frustration tolerance” development in adolescence are determined.
Keywords: adolescence; crisis of identity; frustration tolerance; юность; кризис идентичности; фрустрационная толерантность; юнацтво; криза ідентичності; фрустраційна толерантність; кафедра ділової іноземної мови та міжнародної комунікації